PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO ANIMASI TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SD - Rizka Selviana Putri; Siska Mega Diana; Siti Nuraini; Frida Destini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem in this study was the low critical thinking skills of fifth-grade students at SD Negeri 8 Metro Utara. This study aimed to determine the effect of the Problem Based Learning model assisted by animated video media on the critical thinking skills of fifth-grade elementary school students. The method used in this research was a quantitative approach with a quasi-experimental group design, specifically a non-equivalent control group design. The population and sample of this study consisted of all fifth-grade students of SD Negeri 8 Metro Utara, totaling 36 students, with 17 students as the experimental class and 19 students as the control class. Data collection techniques used in this study included tests in the form of essay questions prepared based on critical thinking indicators, as well as non-test techniques such as observation sheets and documentation. Data analysis using a simple linear regression test showed that H₀ was rejected and Hₐ was accepted. Therefore, the results of the study indicated that there was an effect of the Problem Based Learning model assisted by animated video media on the critical thinking skills of fifth-grade students at SD Negeri 8 Metro Utara in the 2025/2026 academic year.